An automatic method for pottery fragments analysis. (November 2018) - Di Angelo, L.; Di Stefano, P.; Pane, C.
Highlights: A new computer-aided method aimed to analyse pottery fragments is proposed. Starting from a 3D discrete model, it analyses geometrical differential properties. It firstly segments fragment in typical geometrical and morphological features. Then it proceeds with the dimensional analysis of selected recognised features. The results shown an accuracy and robustness not achievable with traditional method. Abstract: With the aim to reduce the uncertainties of the traditional archaeological approach and reduce costs for ceramic investigation, in this paper a computer-based method is proposed. A discrete geometric model of a pottery fragment is the starting input, from which a first distinction in axially and not-axially symmetric surfaces can be done. Geometrical and morphological features are then recognized. Only once that all this information is obtained, it is possible to proceed with the dimensional analysis. The analysis carried on the test case here illustrated proves that the automatic method presents accuracy and robustness not achievable even using the best application of the archaeological method. This method seems to be functional to other goals, such as for pottery classification and reconstruction of ancient ceramics.